5th International Reindeer/Caribou Symposium, 18-22 August 1988, Arvidsjaur, Sweden. - Skjenneberg (ed. in chief), Sven (Rangifer, 1990)
Proceedingsof theFifth International Reindeer/Caribou Symposium, Arvidsjaur, Sweden 18 - 22 August, 1988